The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/ijhcqa-11-2016-0175
|View full text |Cite
|
Sign up to set email alerts
|

A study of deficiencies in teamwork skills among Jordan caregivers

Abstract: Purpose The purpose of this paper is to present the deficiencies in teamwork skills at Jordan hospitals as seen by team members. The study aims to identify training needs to improve teamwork-related soft skills of caregivers to enhance staff satisfaction and improve quality of care. Moreover, the paper provides a methodology to identify the training needs in any healthcare workplace by repeating the same questionnaire. Design/methodology/approach A self-administrated questionnaire was designed to study deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Thus, in the United States in 2006, a similar study demonstrated that, according to employers, the least developed graduates' soft skills are precisely the skills of interaction and creative approach to the performance of labor functions (Are They Really Ready to Work?...). The need to improve teamwork skills and its direct connection with the quality of work, for example, the quality of medical services provided, is also indicated by a later study (Al-Araidah et al, 2018). In 2010 in the United Kingdom of Great Britain and Northern Ireland, Slovenia, Romania and Austria the results of some studies, which analyzed the quality of the graduates' labor market and their ability to meet the needs of employers, were published (Andrews & Higson, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, in the United States in 2006, a similar study demonstrated that, according to employers, the least developed graduates' soft skills are precisely the skills of interaction and creative approach to the performance of labor functions (Are They Really Ready to Work?...). The need to improve teamwork skills and its direct connection with the quality of work, for example, the quality of medical services provided, is also indicated by a later study (Al-Araidah et al, 2018). In 2010 in the United Kingdom of Great Britain and Northern Ireland, Slovenia, Romania and Austria the results of some studies, which analyzed the quality of the graduates' labor market and their ability to meet the needs of employers, were published (Andrews & Higson, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Studies in the field of soft skills are still carried out. The subject of the study is the diagnosis and evaluation of soft skills (Balcar et al, 2018;Mohamed et al, 2017;Brooks et al, 2018;Devedzic et al, 2018); the use of various approaches, methods and techniques, for example, interdisciplinary design work (Vogler et al, 2018), group work (Al-Araidah et al, 2018;Chasidim et al, 2018;Brooks et al, 2018;Yehia & Gunn, 2018;Espey, 2018;Kusumoto, 2018); the development of some certain skills, for example, collaboration skills (Kaburise, 2016;Al-Araidah et al, 2018), critical thinking (Espey, 2018), etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthcare professions, soft skills enhance critical thinking, decision-making, and patient-centered care, which are paramount to quality healthcare delivery and favorable patient outcomes; yet, healthcare educators have traditionally placed a greater emphasis on profession-specific skills [ 3 , 4 ]. Prior studies assessing soft skills training across multiple medical universities found limited emphasis on teamwork and professional communication [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%